Quantification of amylose, amylopectin, and β-glucan in search for genes controlling the three major quality traits in barley by genome-wide association studies - Shu, Xiaoli; Rasmussen, Søren K. (Frontiers in Plant Science, 2014)
Genome-wide association studies (GWAS) for amylose, amylopectin and β-glucan concentration in a collection of 254 European spring barley varieties allowed to identify 20, 17 and 21 single nucleotide polymorphic (SNP) markers, respectively, associated with these important grain quality traits. Negative correlations between the content of amylose and β-glucan (R=-0.62, P<0.01) and amylopectin and β-glucan (R= -0.487, P<0.01) were found in this large collection of spring barley varieties. Besides HvCslF6, amo1 and AGPL2, sex6 and waxy were identified among the major genes responsible for β-glucan, amylose and amylopectin content, respectively. Several minor genes like HvGSL4, HvGSL3 and HvCesA6, PWD were also detected by GWAS for the first time. Furthermore, the gene encoding β-fructofuranosidase, located on the short arm of chromosome 7H at 1.49cM, and SRF6, encoding ‘leucine-rich repeat receptor kinase protein’ on chromosome 2H, are proposed to be new candidate genes for amylopectin formation in barley endosperm. Several of the associated SNPs on chromosome 1H, 5H, 6H and 7H mapped to overlapping regions containing QTLs and genes controlling the three grain constituents. In particular chromosomes 5H and 7H carry many QTLs controlling barley grain quality. Amylose, amylopectin and β-glucan were interacted among each other through a metabolic network connected by UDP showing pleiotropic effects. Taken together, these results showed that cereal quality traits related each other and regulated through an interaction network, the identified major genes and genetic regions for amylose, amylopectin and β-glucan is a helpful for further research on carbohydrates and barley breeding.